Pelatihan Kewirausahaan Praktis untuk Santri MA Biroyatul Huda: Membentuk Santri Produktif dan Mandiri - Citaningati, Putri Rizka; Naylah, Maal; Purwanti, Evi Yulia; Pujiyono, Arif; Widodo, Wahyu (Yayasan Sagita Akademia Maju, 2025)
This community service activity aims to improve the understanding and entrepreneurial skills of students at MA Biroyatul Huda, Banyumas Regency. Students, as part of the younger generation, have great potential to develop productive, economically valuable businesses based on Islamic values. Through this practical entrepreneurship training, participants will be equipped with basic knowledge on starting a business, simple financial management, and contextual marketing strategies. The activity is conducted through a participatory approach, using interactive lectures, group discussions, and business plan simulations. It is hoped that this activity will shape students who are independent, creative, and competitive, and support local economic development based on Islamic boarding schools.